Impact of the Effluents of Hyderabad City, Tando Muhammad Khan, and Matli on Phuleli Canal Water - Mahessar, A. A.; Qureshi, S.; Qureshi, A. L.; Ansari, K.; Dars, G. H. (Engineering, Technology & Applied Science Research, 2020)
The demand and supply of safe water is a basic need. The consumption of clean water intensified with population growth and economic development which in turn cause degradation of available freshwater resources while creating huge volumes of wastewater, solid waste, and serious environmental problems. This paper presents the impact of disposing of domestic/industrial effluents into an irrigation canal. The subsequent contamination of the canal water becomes a public health risk. The non-perennial Phuleli canal with a discharge of 15,026 cusecs, takes in water from the left bank of Kotri Barrage, which is the last controlling hydraulic structure on the Indus River. This canal runs from the periphery of Hyderabad, Tando Muhammad Khan (TM Khan) and Matli cities and supplies water for domestic, agricultural, and industrial activities. The canal water is the only source of drinking water for millions of people because the groundwater in the command area of the canal is highly saline. The banks on both sides of the canal have encroached in cities’ areas. The huge volume of solid waste and municipal and industrial wastewater from these cities and from the occupied canal banks are dumped directly into the canal without any treatment. The collected samples’ were analyzed for pH, EC, TDS, Cl, SO4, HCO3, hardness, Na, K, Ca, and Mg. These results show higher than permissible limits as per NEQS and WHO. The Karl Pearson matrix correlation of parameters reveals strong relation among EC with TDS and CL with SO4, Mg with K and moderated relationship among the other parameters except for pH and DO. Water Quality Index (WQI) model indicates that the water quality of the canal is poor and unfit for drinking. Hence the consumption of canal water is a high potential health risk for locals.